Gilbert Syndrome Unveiled: A Rare Presentation Pattern of Gilbert Syndrome Phenotype - Jose, Neethu; Mathew, Betsy (Indian Journal of Pharmacy Practice)
Gilbert syndrome is a relatively common, benign liver condition characterized by elevated levels of unconjugated bilirubin in the blood. In this instance, we present the case of an 18-year-old woman who developed jaundice subsequent to receiving a blood transfusion for iron deficiency anemia. Initially, the manifestation was suspected to be a haemolytic transfusion reaction, but further examination revealed that unconjugated hyperbilirubinemia was not linked to haemolysis. The patient reported a history of mild, self-limiting, recurrent jaundice episodes. A clinical diagnosis of Gilbert syndrome was established, and remarkably, bilirubin levels gradually normalized without any interventions. This case highlights an atypical presentation of Gilbert Syndrome.
Keywords: . Keywords: Gilbert syndrome; Hyperbilirubinemia; Jaundice; Transaminases